1994
DOI: 10.1007/bf02600301
|View full text |Cite
|
Sign up to set email alerts
|

Beta blocker use in the treatment of community hospital patients discharged after myocardial infarction

Abstract: A minority of patients discharged after acute myocardial infarction receive beta blocker therapy, and women are only half as likely as men to receive it, after controlling for other factors. Though there are no data relating to whether calcium channel blockers or angiotensin-converting enzyme inhibitors lessen the protective effect of beta blocker therapy post-acute myocardial infarction, it would appear that these agents are frequently being used in lieu of beta blocker therapy for post-acute myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
5
25
2
Order By: Relevance
“…10 In the current study, we also found that the use of evidence-based drug therapies decreased with increasing patient age, a finding that is consistent with previous studies. 16,17 In this regard, our findings build upon those prior studies, by demonstrating that the importance of age in influencing prescribing patterns persists after adjustment for physician, hospital and community characteristics. Similarly, the impact of the specialty of the attending physician on the use of evidence-based drug therapies builds upon previous evidence of lower prescribing rates of β-blockers among general practitioners and family practitioners than among cardiology specialists.…”
Section: Discussionsupporting
confidence: 82%
“…10 In the current study, we also found that the use of evidence-based drug therapies decreased with increasing patient age, a finding that is consistent with previous studies. 16,17 In this regard, our findings build upon those prior studies, by demonstrating that the importance of age in influencing prescribing patterns persists after adjustment for physician, hospital and community characteristics. Similarly, the impact of the specialty of the attending physician on the use of evidence-based drug therapies builds upon previous evidence of lower prescribing rates of β-blockers among general practitioners and family practitioners than among cardiology specialists.…”
Section: Discussionsupporting
confidence: 82%
“…4,6,8,9,14 Some of the estimates were even lower than what we report. For example, Soumerai and colleagues 9 merged 3 large administrative databases with data from 1987 through 1992 to examine the use of ␤-blockers among elderly survivors of AMI from New Jersey.…”
Section: Commentcontrasting
confidence: 82%
“…Similar to the findings of another investigator with a similar-sized cohort, 18 logistic regression analysis did not suggest any association with race. But the small number of black patients did not provide adequate power to examine this question.…”
Section: Discussionsupporting
confidence: 88%
“…1,9,[14][15][16][17][18][19][20][21][22] As seen in previous studies by other investigators, 23 is unlikely to account for increase in use of BBs, because this group has consistently been found to be undertreated. The increase in prescription of BBs prehospital, in hospital, and at discharge is most likely the result of many quality improvement measures that occurred between the study periods.…”
Section: Discussionmentioning
confidence: 71%